Evaluasi Pembelajaran Nontes Dalam Mata Pelajaran Akhlak di SMA MUH 1 Karanganyar - Afief Thiar Ramadhan; Ardiansyah Sulistiyanto; Muhammad Irfani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to determine the implementation of non-test evaluation on Akhlak learning at SMA MUH 1 Karanganyar. The method used is a qualitative method (qualitative description) with the aim of describing, analyzing phenomena, events and evaluating Aqidah Moral learning activities carried out by teachers for class 11 students at SMA MUH 1 Karanganyar. The data collection techniques used were observation, interviews with teachers, interviews with school principals, documentation, field notes, and triangulation. Triangulation is a data collection technique that combines several existing data merging techniques data source. The results of the research show that in general the quality of Akhlak learning at MUH 1 Karanganyar Vocational School has been running well. Likewise, the learning outcomes are also good results. However, in implementing this learning there are also things that need to be done aimed at improving learning programs.